Contemporary sociological inquiry on the “nature” - Garavito González, Leonardo (Universidad del Rosario, 2010)
This text roughly presents the main insights and challenges in contemporary sociology about how the human-nature relationship is being understood. It starts by dealing with the problem of conceptualizing the very idea of nature. Afterwards, it presents the theoretical model of social construction of nature. As a complement, it poses the question ¿What can it be done after the social-nature relational crisis? so that it illustrates a set of answers given from the diverse political-ecology’s points of view, on how to act about it. Finally, this article concludes that although the society-nature relational problems are being increasingly recognized by modern societies, we are far from a consensual strategy to deal with the contemporary cultural domination-over-nature model, as well as its ecological and social risks.